Subsidy reforms in the Middle East and North Africa: Strategic options and their consequences for the social contract - Georgeta Vidican Auktor; Markus Loewe (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
After independence, energy and food subsidies became a cornerstone of the social contracts in the Middle East and North Africa (MENA) countries. Governments spent heavily to reduce poverty and strengthen their own legitimacy. However, as government rents faded, subsidy spending became financially unsustainable and foreign donors pressed for reforms. Yet, reform has been challenging for all the governments as subsidies affect all consumers, therefore raising the risk of government delegitimisation. Several publications have analysed the subsidy reforms of various MENA countries, but few have systematically analysed their impacts on the prevailing social contracts. This paper shows that reforms in a key policy field such as subsidy spending can affect the nature of social contracts profoundly and distinctly, depending on the reform strategy. It assesses the reform processes that took place in Morocco, Egypt and Iran primarily between 2010 and 2017, thus before the United States once more tightened sanctions against Iran and before the COVID-19 pandemic broke out. We argue that governments applied distinct strategies to reduce subsidy spending without provoking major social unrest to reforms, with the effect that the social contracts of the three countries changed in quite different ways. Morocco's government removed most subsidies, especially those that predominantly benefitted the middle-class. [...]
Keywords: 330; Subsidy reform; government spending; social contract; government legitimacy; social policy; Middle East and North Africa; Morocco; Egypt; Iran; protection; provision; political participation; subsidies; social cash transfers; public dialogue; information of public policies; repression; compensation measures